2013
DOI: 10.1038/ncomms3726
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-mediated activation of Caenorhabditis elegans CED-8 promotes apoptosis and phosphatidylserine externalization

Abstract: During apoptosis, phosphatidylserine (PS), normally restricted to the inner leaflet of the plasma membrane, is exposed on the surface of apoptotic cells and serves as an “eat-me” signal to trigger phagocytosis. It is poorly understood how PS exposure is activated in apoptotic cells. Here we report that CED-8, a C. elegans protein implicated in controlling the kinetics of apoptosis and a homolog of the XK family proteins, is a substrate of the CED-3 caspase. Cleavage of CED-8 by CED-3 activates its proapoptotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
76
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 39 publications
2
76
0
Order By: Relevance
“…We and others showed previously that Xkr8/CED-8, predicted to carry six transmembrane regions, is essential to expose PtdSer during apoptosis (8,13). In the present study, we found that Xkr4 and Xkr9 along with Xkr8 of the mammalian Xkr family support the PtdSer exposure in response to apoptotic stimuli.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…We and others showed previously that Xkr8/CED-8, predicted to carry six transmembrane regions, is essential to expose PtdSer during apoptosis (8,13). In the present study, we found that Xkr4 and Xkr9 along with Xkr8 of the mammalian Xkr family support the PtdSer exposure in response to apoptotic stimuli.…”
Section: Discussionsupporting
confidence: 64%
“…A null mutation of mouse Xkr8 or the epigenetic repression of the XKR8 gene expression in human cancer cells blocks PtdSer exposure during apoptosis. Caenorhabditis elegans carries one Xkr homolog (CED-8) with a caspase recog-nition sequence in the N-terminal tail, and its cleavage by CED-3 (caspase in C. elegans) causes PtdSer to be exposed on the surface of the dying cell during programmed cell death (8,13).…”
mentioning
confidence: 99%
“…CED8 has a caspase (CED3)-recognition site in its N terminus 71 and is indispensable for CED3-dependent PtdSer exposure. 66 On the other hand, a Drosophila ortholog (CG32579) has no apparent caspaserecognition site, and it is not clear how this molecule is activated or whether it is involved in apoptotic PtdSer exposure.…”
Section: Caspase-dependent Scramblasesmentioning
confidence: 99%
“…66 Similarly, mutations in CED8, an Xkr8 ortholog in nematodes, causes the failure of PtdSer exposure in dying cells, and the inefficient or delayed engulfment of dead cells. 71 Masking PtdSer or deleting molecules that recognize PtdSer, such as MFG-E8, Tim4 and TAM receptors, blocks the engulfment of apoptotic cells, and induces the development of systemic lupus erythematosus-type autoimmune diseases. [97][98][99][100][101] Thus, it is likely that Xkr8-deficient mice develop similar autoimmune diseases, but this remains to be confirmed.…”
Section: Defects In Flippases and Scramblasesmentioning
confidence: 99%
See 1 more Smart Citation